Effect of Underground Corrosion on the Buckling of Al Alloy 6061-T4 Columns under Increasing Load - Khenyab, Ali Yousuf; Ajaj, Hussein Fadhil; Helal, Rawa Ahmed (Al-Nahrain Journal for Engineering Sciences, 2018)
This research deals with the extent to which corrosion affects the behavior of buckling for 6061-T4 aluminum alloy under increasing compressive dynamic loads. Two types of columns, long, and intermediate were used.1% of the length column is the allowable lateral deflection. This is called the critical buckling of the columns. For the purpose of calculating the critical deflection, a digital dial gauge was used and set at a distance of 0.7 of column length from the fixed end condition for the column. The experimental analysis revealed that the corrosion time negatively affects the mechanical properties of materials such as the corroded specimens of 60 days (The least time to observe the corrosion of aluminum in the soil) which have approximately 2.7 % reduction in ultimate strength compared with the non-corroded specimen.  Increasing the corrosion time reduces the critical load such as the maximum reduction will be 4.24% in critical buckling load for 60 days’ corrosion time. The results obtained were experimentally compared with the theoretical formulas of the Perry-Robertson and Euler-Johnson formula with the results of the ANSYS. It was found that the Perry-Robertson formula has a good agreement with the experimental results with a safety factor of 1.2, while the Euler-Johnson formula agreed with the experimental results taking a safety factor of 1.5. The ANSYS results showed a good agreement between the measured and calculated values by taking 1.1 factor of safety.